2003
DOI: 10.1016/s0040-4039(02)02523-6
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki cross-coupling reaction of aryl halides with arylboronic acids catalysed by Pd(II)-NaY zeolite

Abstract: Abstract-Pd(II)-exchanged NaY zeolite showed high activity in the Suzuki cross-coupling reactions of aryl bromides and iodides without added ligands. The DMF:water ratio, and the type and amount of base were found to be critical for the efficiency of the reaction. The catalyst is reusable after regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Pd-loaded NaY catalysts evidently worked at very high TONs, and we already showed that the catalyst can be re-used in the SM reactions of aryl bromides at room temperature with Pd concentration of 2.5 mol% after regeneration [23,24]. Nevertheless, we have determined in this study that the catalyst is not quite re-usable at low Pd loadings.…”
Section: Suzuki-miyaura Reactions Of Aryl Bromides In Water-polar Aprmentioning
confidence: 67%
See 4 more Smart Citations
“…Pd-loaded NaY catalysts evidently worked at very high TONs, and we already showed that the catalyst can be re-used in the SM reactions of aryl bromides at room temperature with Pd concentration of 2.5 mol% after regeneration [23,24]. Nevertheless, we have determined in this study that the catalyst is not quite re-usable at low Pd loadings.…”
Section: Suzuki-miyaura Reactions Of Aryl Bromides In Water-polar Aprmentioning
confidence: 67%
“…Alkali carbonates were the only bases screened in this study since they had been marked, previously, as being the most suitable base types for the SM coupling activity of palladium-loaded NaY zeolites [23,24]. In this study, sodium carbonate was observed to be the most efficient base when the reactions were performed in a DMF/water mixture (1/1).…”
Section: Suzuki-miyaura Reactions Of Aryl Bromides In Water-polar Aprmentioning
confidence: 85%
See 3 more Smart Citations